The Influence of Discipline, Quality of Work Life, and Self-Efficacy on the Performance of Early Childhood Education Teachers in Gunung Sindur District - Purwanti, Purwanti; Anwar, Saiful; Zubaidah, Siti (Paidea : Jurnal Pendidikan dan Pembelajaran Indonesia, 2025)
This study provides an integrated analysis of the effects of work discipline, quality of work life, and self-efficacy on the performance of Early Childhood Education teachers in Gunung Sindur District, with particular emphasis on identifying the most influential determinant of performance. Using a quantitative survey design, data were collected from teachers selected through purposive sampling based on predefined professional criteria. Structured questionnaires were administered and analyzed using multiple regression techniques to examine both partial and simultaneous relationships among the variables. The findings reveal that all three variables significantly and positively influence teacher performance; however, self-efficacy emerges as the dominant predictor, indicating that teachers’ belief in their own capabilities plays a more decisive role than organizational or environmental factors alone. This integrated evidence underscores that while supportive working conditions and discipline remain important, strengthening teachers’ self-efficacy is central to optimizing performance. The study contributes to the literature by highlighting self-efficacy as a key leverage point in improving early childhood teacher performance and suggests that institutional policies and professional development programs should prioritize strategies that enhance teachers’ confidence, autonomy, and professional competence to improve the overall quality of early childhood education.